Działalność Fundacji Pomocy Humanitarnej „Redemptoris Missio” odpowiedzią na wyzwania encykliki Jana Pawła II - Borucka, Monika (Annales Missiologici Posnanienses, 2012)
Foundation of the Humanitarian Aid „Redemptoris Missio” was established in 1992 r. in Poznañ. It is a fruit of the encyclical of John Paul II on the permanent validity of the Church’s missionary mandate. The foundation forms the specialist medical backup for missionary centers. It organizes the medical and financial help as well as propagates the knowledge about missions and missionaries. It also carries a publishing activity. It gives a witness on the service of lay Christians in the missionary activities.